PERANCANGAN APLIKASI SISTEM INFORMASI KEPENDUDUKAN DI KECAMATAN GONDOMANAN - Dwi Broto Bagus Setiawan (Universitas PGRI Semarang, 2016)
Information technology development is very fast in the last decade was veryinfluential on various aspects of life in the world in general and Indonesia in particular.Especially offices that have access to large data processing, because the data processing is nolonger possible to use the manual method because it is less effective and efficient. Likewise withGondomanan District, Yogyakarta are still using simple applications such as excel in the sensethat less rapidly. For that create an information system that could facilitate performancekepependudukan Gondomanan District, Yogyakarta. With the use of information systems, it is possible the optimization of the work and service functions to achieve good services as needed,including the optimization of the system in the handling of population, especially in theinformation system that could facilitate performance kepependudukan Gondomanan District,Yogyakarta. Then produced an information system that is easy, interactive, fast, and useful. Thesystem uses the Apache server, PHP programming language and MySQL database